الخوارزمية الرياضية الناظمة لاستقرار منظومة الطاقة الكهربائية عن طريق التحكم ببارامترات محطات التوليد الكهرومائية - زياد هرموش (Tishreen University, 2019)
تتصف محطات التوليد الكهرومائية بإنتاج و توليد الطاقة الكهربائية باستطاعات كبيرة مما يعطيها أهمية خاصة، كما يضفي اهتماماً خاصاً على عمليات التحكم المرافقة لعمل هذا النوع من المحطات، لاسيما أننا، في سورية، نملك محطة توليد كهرومائية على سد الفرات قيد العمل. يسهم هذا البحث في إلقاء الضوء على الإمكانيات المتاحة لرفع استقرار منظومة القدرة الكهربائية، من خلال تطوير خوارزمية رياضية للتحكم ببارامترات الاستطاعة الكهربائية المولدة من هذا النوع من المحطات، التي تستخدم أساساً لدعم حمولات الذروة كون إقلاعها سلس و سريع. تعتمد هذه الخوارزمية على دراسة نظام التحكم، باستطاعة التوربينات الضخمة للمحطة الكهرومائية، التي تضمن الحصول على زمن قصير لتنزيل حمولة التوربين، وذلك من أجل رفع الاستقرار الديناميكي لمنظومة القدرة الكهربائية عند دارات القصر الكبيرة، و ذلك لضمان تقييد استطاعة التوربين(العنفة) من أجل زيادة الاستقرار الستاتيكي عند فصل خطوط نقل القدرة الكهربائية من أجل ضمان تخميد الحالات العابرة الكهروديناميكية. The electrohydrolic stations are producing and generating electrical power in huge quantities  that makes them significantly important; this also creates a particular essentiality for control process associated with the job of these types of stations. Especially, we have a remarkable electrohydrolic station in Syria that is located in Euphrates Dam. This paper is studying the available capability of increasing the electrical power system stability through developing mathematical algorithm for controlling the electrical power generated from these types of stations which are used basically to support the peak loads due to smooth and quick start. This algorithm is based on studying the control system of huge turbines power for electrohydrolic stations, which guarantee obtaining a short time to decrease the turbine load in order to increase the dynamic stability of electrical power system when short circuit occurred, and that will assure the turbine power limits for increasing the static stability at turning off the electrical power transmission lines and also confirm the electrodynamics transient process dampen.